ChemInform Abstract: Highly Ordered Mesoporous Cobalt‐Containing Oxides: Structure, Catalytic Properties, and Active Sites in Oxidation of Carbon Monoxide. Issue 52 (10th December 2015) - Gu, Dong; Jia, Chun‐Jiang; Weidenthaler, Claudia; Bongard, Hans‐Josef; Spliethoff, Bernd; Schmidt, Wolfgang; Schueth, Ferdi
Abstract: Mesoporous CoO is prepared by H2 reduction of nanocast Co3 O4 at 250 °C for 1.5 h.